2020
DOI: 10.1108/ec-09-2019-0420
|View full text |Cite
|
Sign up to set email alerts
|

Seismic structural responses reduction of double-layered containment nuclear power plant via BIS-TMD

Abstract: Purpose In recent years, a new type of double-layered containment structure of nuclear power plant has been built in China, named ACP1000 NNP. This paper aims to propose a new method to mitigate the seismic responses of this type of the structure. Design/methodology/approach The new base isolation structure (BIS)- tuned mass damper (TMD) structure was proposed and implemented only by modifying the connection between various components of NPPs, and the application of this concept design in ACP1000 was skillfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Over the past few decades, at least four NPP accidents that exceeded the seismic design level have been recorded in Japan alone. 1 Seismic response analysis of nuclear island (NI) buildings is key work of structural design of NPPs. As the stiffness and weight of NPP buildings are significant and the soil of sites is relatively soft, the soil-structure interaction (SSI) effect for the seismic response analysis of NPPs has become an important issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, at least four NPP accidents that exceeded the seismic design level have been recorded in Japan alone. 1 Seismic response analysis of nuclear island (NI) buildings is key work of structural design of NPPs. As the stiffness and weight of NPP buildings are significant and the soil of sites is relatively soft, the soil-structure interaction (SSI) effect for the seismic response analysis of NPPs has become an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Although this isolation technology has been widely deployed for industrial and civil buildings, bridges, and certain types of infrastructure, its application in NPPs is limited. The main reasons for the limited use of seismic isolation technology in NPPs, its development, and future research needs have been presented and identified in numerous papers 1,8,9 . Among all NPPs currently in commercial operation worldwide, only Koeberg in South Africa and Cruas in France have adopted this base isolation technology, wherein neoprene rubber bearings, including flat sliders in some installations, have been used to isolate the horizontal components of ground motion 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional seismic design of structures, the seismic resistance of structures is enhanced by increasing the strength of the structural components. More recently, several new passive and active techniques have been developed to reduce the impact of earthquakes (Domenico et al , 2020a; Peng et al , 2019; Domenico and Ricciardi, 2018; Hou et al , 2020; Domenico et al , 2020b; Matteo et al , 2018), one of which is to equip structures with seismic base isolation systems to reduce the seismic demand of structures (Petti et al , 2010; Domizio et al , 2015; Kelly, 2008). The seismic base isolation system has been studied and developed extensively in the last few decades by several research institutions and has emerged as one of the most effective strategies to protect infrastructure from seismic hazards, especially in high seismic regions (Domenico et al , 2020c; Markou et al , 2018; Luca and Guidi, 2019, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst all NPPs currently in commercial operation worldwide, only Koeberg in South Africa and Cruas in France have adopted the base isolation technology, in which neoprene rubber bearings, including flat sliders in some installations, have been used to isolate the horizontal components of ground motion (Coladant, 1991; Lo Frano, 2018). The main reasons for the limited use of seismic isolation in NPPs, its development and future research needs have been presented and identified in numerous papers (Hou et al , 2020; Whittaker and Kumar, 2014; Whittaker et al , 2018). Based on many new theories and techniques, the base isolation of NPPs in the horizontal direction has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation